La universidad pública y retos institucionales - Romero Pérez, Jorge Enrique (2017)
Article 84 of the Constitution provides public or state universities with a juridical system of autonomy or independence that has been defined and characterized by the Constitutional Court when responding to the consultations filed for settlement. This essay presents some judgments or decisions of the Constitutional Court that may be related to the issue of violation of university autonomy by the police force of the Ministry of Public Security and the Judicial Investigation Department (OIJ) on Monday, April 12, 2010; being this an event that occurred for the first time in the history of the University of Costa Rica.